Analisis Pengaruh Keputusan Pembelian pada Kosmetik Berlabel Halal - Ratih Hesty Utami Puspitasari (Business Management Analysis Journal (BMAJ), 2019)
This research aims to analyze the significant influence between halal labels, and price perceptions of Wardah's cosmetics purchasing decisions on Wardah counter consumers in the ADA Semarang supermarket. This study used descriptive quantitative methods. The population used is all consumers of the Wardah Swalayan ADA Semarang counter, with a total sample of 100 respondents taken using a purposive sampling technique. Data were analyzed through regression analysis using SPSS version 22. Results of the regression analysis in this study are Halal labels have a positive significant effect on purchasing decisions and price perception has a positive and significant effect on purchasing decisions.